Silverpoint and metalpoint drawing a complete guide to the medium - Schwalb, Susan 1944-; Mazzullo, Tom 1968- (New York, New York Routledge, 2019)
Silverpoint, and metalpoint more generally, is the practice of marking with soft metal on a specifically prepared drawing surface. Practiced for centuries, the artform is experiencing a resurgence in recent years, with contemporary work exploring abstract as well as realist, conceptual as well as traditional. Silverpoint and Metalpoint Drawing is the essential manual of metalpoint technique, written by Susan Schwalb and Tom Mazzullo, contemporary masters of the medium. This book is the first treatise on the subject for artists and art teachers with chapters on early history, materials including grounds, supports, metals, and tools, techniques for working in metalpoint as well as mixed media, and finally, the care of metalpoint works. Not only beautifully illustrated, this book also demonstrates how to photograph and exhibit metalpoint art. Featuring a gallery of drawings by contemporary artists, along with their tips and insight, Silverpoint and Metalpoint Drawing is a perfect introduction for students of the medium and an inspiration for those already more familiar with it.
Preface: Why Metalpoint Now?-- Introduction: What is Silverpoint and Metalpoint?-- Chapter 1: The History of Metalpoint As a Drawing Technique by Thea Burns-- Chapter 2: Tools, Metals, and Tarnishing-- Chapter 3: Grounds, Preparation, and Supports-- Chapter 4: Drawing with Metalpoint-- Chapter 5: Mixed Media by Carol Prusa-- Chapter 6: Storing, Framing, Photographing, and Shipping Metalpoint Work-- Chapter 7: Contemporary Metalpoint Drawing--
Includes bibliographical references and index
Keywords: Metalpoint drawing -- Technique; Silverpoint drawing -- Technique